X-ray Diffraction Analysis of ProRoot Mineral Trioxide Aggregate Hydrated at Different pH Values - Akhavan, Hengameh; Mohebbi, Pooneh; Firouzi, Amir; Noroozi, Mehdi (Iranian Endodontic Journal, 2016)
Introduction: The aim of this study was to compare the chemical compounds of white ProRoot mineral trioxide aggregate (WMTA) hydrated at different pH environments. Methods and Materials: Mixed samples of WMTA were kept in acidic (pH=5.4), neutral (pH=7.4) and alkaline (pH=9.4) environments for 48 h. Then, X-ray diffraction (XRD) analysis was performed for both hydrated and powder forms of WMTA. Portlandite crystalline structures of environments were compared from three aspects: intensity (height of the peak, corresponding to the concentration), crystallinity (peak area/total area) and crystal size (full-width at half-maximum of the peak). Results: After matching the peaks of each sample with those of the International Center for Diffraction Data (ICDD) database, the main constituent of all set cements and powder form was found to be bismuth oxide. Acidic environment exhibited lower intensity and crystallinity of portlandite in comparison with neutral environment. Conclusion: The highest concentration and crystallinity of portlandite were observed in WMTA samples hydrated at neutral pH and the highest crystal size was detected after hydration in alkaline pH. Keywords: Mineral Trioxide Aggregate; pH; X-ray Diffraction